Native carbonoxidation microorganisms in bioremedetion Northern Caspian sea from oil pollution - V. V. Gridneva; I. J. Kulikova (Юг России: экология, развитие, 2015)
The 26 strains microorganisms - degradation oil have been isolated from shelf water North Caspian. The high emulsifying ability relative to benzine, kerosene and diesel-fuel oil relevantly were possessed the 11 strains. The 4 cultures exhibiting degradation of oil rates 43-49 %, respectively, were selected.